Numerical investigation of a novel tube design for the geothermal borehole heat exchanger - Bouhacina, Benamar; Saim, Rachid; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2015)
The fins are mainly used to enhance the heat transfer in several energy systems and one of them is the geothermal borehole heat exchanger (GHE). Therefore, the idea of adding longitudinal fins on the inner smooth surface of the (GHE)'s tube to ensure the better heat transfer and getting it well enhanced, as it is investigated numerically in this present paper. Then the effects and the benefits of this new design of high density polyethylene (HDPE) finned tube is studied and the thermal and dynamic comportment of a typical vertical GHE is evolved. For this two different three-dimensional numerical models having the same cell number, boundary and initial conditions representing respectively the smooth and the finned U-tube GHEs are constructed under the Fluent software, The model of the smooth U-tube GHE is validated by a comparison between its numerical results and experimental data, then confirmed by a final comparing to those of the finned U-tube GHE, the results show that the fins have a great effect in the thermal and dynamic performance of GHEs, improve heat extraction from soil around 7%, and enable a faster temperature recovery, which is good for enhancing the GCHPs systems performances. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: 3D numerical simulation; Ground heat exchanger; Finned U-tube